The Intentionality of Markiian Shashkevych’s Ukrainian Language Sermons - Філон, Микола Іванович; Бутко, Софія Григорівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article considers some aspects of the intentional arrangement of Markiian Shashkevych’s Ukrainian language sermons. The constituents of the linguistic image of the preacher are highlighted, the intentional polyfunctionality of Markiian Shashkevych’s preached word is characterized, the connection of the sermons linguistic organization with some elements of the national linguistic world image as well as with the Ukrainians’ peculiar world perception and world outlook is defined, the specific character of the sermons linguistic organization by means of the folk word in the context of realizing the orientation towards religious communication with the reader is accentuated. It was revealed that the semantic capaciousness of father Markiian’s word is gained through organic combination of the images of Christian, folk, bookish and spoken, universal and nationally specific discourses. The intentionality of Markiian Shashkevych’s Ukrainian Language sermons is not only realized through the speaker’s wish to hand down the values of Christian life to the believers and to turn such values into constants of the hearers’ spiritual world, but also by means of the folk world to influence the formation of the Ukrainian language religious personality as a necessary condition of forming the national linguistic personality in general.